2012
DOI: 10.1261/rna.032409.112
|View full text |Cite
|
Sign up to set email alerts
|

Structure and folding of a rare, natural kink turn in RNA with an A•A pair at the 2b•2n position

Abstract: The kink turn (k-turn) is a frequently occurring motif, comprising a bulge followed by G d A and A d G pairs that introduces a sharp axial bend in duplex RNA. Natural k-turn sequences exhibit significant departures from the consensus, including the A d G pairs that form critical interactions stabilizing the core of the structure. Kt-23 found in the small ribosomal subunit differs from the consensus in many organisms, particularly in the second A d G pair distal to the bulge (2b d 2n). Analysis of many Kt-23 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…The other k-turns shown are those of U4 snRNA (Vidovic et al 2000), H. marismortui Kt-38 (Ban et al 2000), the SAM-I riboswitch (Schroeder et al 2011) and its G2nA variant, and Thelohania solenopsae (T.s.) Kt-23 (Schroeder et al 2012). …”
Section: K-turns Fall Into Two Structural Classesmentioning
confidence: 99%
See 3 more Smart Citations
“…The other k-turns shown are those of U4 snRNA (Vidovic et al 2000), H. marismortui Kt-38 (Ban et al 2000), the SAM-I riboswitch (Schroeder et al 2011) and its G2nA variant, and Thelohania solenopsae (T.s.) Kt-23 (Schroeder et al 2012). …”
Section: K-turns Fall Into Two Structural Classesmentioning
confidence: 99%
“…In some k-turns, well-exemplified by Kt-23 (Schroeder and Lilley 2009;Schroeder et al 2012), the G normally found at the 2n position is often replaced by a different nucleotide. However, the adenine at the 2b position is usually retained, and it makes equivalent A-minor interactions with the C helix.…”
Section: The Classification Extends To K-turns Without Guanine At Thementioning
confidence: 99%
See 2 more Smart Citations
“…The X-ray crystal structure of the Thermoanaerobacter tengcongensis MetF-H2 SAM-I aptamer domain has been determined bound to SAM, SAH and sinefungin [25, 26]; in its ligand-free state[27]; as a scaffold for understanding the kink-turn motifs[28, 29]; and in complex with the kink-turn binding protein YbxF[30]. In addition, the Bacillus subtilis yitJ SAM-I riboswitch crystal structure was determined in complex with SAM [16].…”
Section: Common Themes and Differences In Sam Recognition Among Samentioning
confidence: 99%